Grandletters: Letter 1 Affection and friendship - Smith, Charles A.; Gutsch, Gayla (My University, 1983)
This publication helps grandparents and grandchildren communicate by teaching them how to write letters to each other.
MF752_1983_12
Keywords: MF752; Home and Family; MF